A Framework for Studying Cost Growth on Complex Acquisition Programs. Issue 6 (21st January 2016) - Dwyer, Morgan; Cameron, Bruce; Szajnfarber, Zoe
ABSTRACT: The government acquisition system is consistently plagued by cost growth and by attempts at acquisition reform. Despite these persistent challenges, the academic community lacks a methodology for studying complex acquisition programs both in‐depth and longitudinally throughout their life cycles. In this paper, we present a framework for studying complex acquisition programs that provides researchers with a strategy for systematically studying cost growth mechanisms. The proposed framework provides a means to identify specific technical and organizational mechanisms for cost growth, to organize those mechanisms using design structure matrices, and to observe the evolution of those mechanisms throughout a program's life cycle. To illustrate the utility of our framework, we apply it to analyze a case study of the National Polar‐orbiting Operational Environmental Satellite System (NPOESS) program. Ultimately, we demonstrate that the framework enables us to generate unique insights into the mechanisms that induced cost growth on NPOESS and that were unacknowledged by previous studies. Specifically, we observed that complexity was injected into the technical system well before the program's cost estimates began to increase and that it was the complexity of the NPOESS organization that hindered the program's ability to effectively estimate and to manage its costs.